Comprehensive Evaluation of the Physicochemical Properties of LnIII Complexes of Aminoethyl‐DO3A as pH‐Responsive T1‐MRI Contrast Agents1. Issue 10 (7th February 2014) - Baranyai, Zsolt; Rolla, Gabriele A.; Negri, Roberto; Forgács, Attila; Giovenzana, Giovanni B.; Tei, Lorenzo
Abstract N‐Substituted aminoethyl groups were attached to 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7‐triacetic acid (DO3A) with the aim to design pH‐responsive LnIII complexes based on the pH‐dependent on/off ligation of the amine nitrogen to the metal ion. The following ligands were synthesized: AE‐DO3A (aminoethyl‐DO3A), MAE‐DO3A (N‐methylaminoethyl‐DO3A), DMAE‐DO3A (N, N‐dimethylaminoethyl‐DO3A) and MEM‐AE‐DO3A (N‐methoxyethyl‐N‐methylaminoethyl‐DO3A). The physicochemical properties of the LnIII complexes were investigated for the evaluation of their potential applicability as magnetic resonance imaging (MRI) contrast agents. In particular, a 1H and 17O NMR relaxometric study was carried out for these GdIII complexes at two different pH values: at basic pH (pendant amino group coordinated to the metal centre) and at acidic pH (protonated amine, not interacting with the metal ion). EuIII complexes allow one to estimate the number of inner‐sphere water molecules through luminescence lifetime measurements and obtain some structural information through variable‐temperature (VT) high‐resolution 1H NMR studies. Equilibria between differently hydrated species were found for most of the complexes at both acidic and basic pH. The thermodynamic stability of CaII, ZnII, CuII and LnIII complexes and kinetics of formation and dissociation reactions of LnIII complexes of AE‐DO3A and DMAE‐DO3A were investigated showing stabilities comparable to currently approved GdIII‐based CAs. In detail, higher total basicity (Σlog KiH) and higher stability constants of LnIII complexes were found for AE‐DO3A with respect to DMAE‐DO3A (i.e., log KGd‐AE‐DO3A=22.40 and log KGd‐DMAE‐DO3A=20.56). The transmetallation reactions of GdIII complexes are very slow (Gd‐AE‐DO3A: t1/2=2.7×104 h; Gd‐DMAE‐DO3A: 1.1×105 h at pH 7.4 and 298 K) and occur through proton‐assisted dissociation.